Actual vs. perceived exertion during active virtual reality game exercise - Stewart, Trenton H.; Villaneuva, Kirsten; Hahn, Amanda; Ortiz-Delatorre, Julissa; Wolf, Chandler; Nguyen, Randy; Bolter, Nicole D.; Kern, Marialice; Bagley, James R. (Frontiers in Rehabilitation Sciences, 2022)
Background: Virtual exercise has become more common as emerging and converging technologies make active virtual reality games (AVRGs) a viable mode of exercise for health and fitness. Our lab has previously shown that active virtual reality games (AVRGs) can elicit moderate to vigorous exercise intensities that meet recommended health benefit guidelines. Dissociative attentional focuses during AVRG gameplay have the potential to widen the gap between participants’ perception of exertion and actual exertion. Objective: The aim of this study was to determine actual exertion (AEx) vs perceived exertion (PEx) levels during AVRGs by measuring heart rate (HR) and ratings of perceived exertion (RPE) in two different settings. Materials & Method: HR and RPE were collected on participants (N = 32; age 22.6 ± 2.6) during 10 minutes of gameplay in LabS and GymS using the HTC VIVE with the following games played: Fruit Ninja VR (FNVR), Beat Saber (BS), and Holopoint (HP). Results: Participants exhibited significantly higher levels of AEx compared to reported PEx for all three AVRGs (Intensity): FNVR [AEx = 11.6 ± 1.8 (Light), PEx = 9.0 ± 2.0 (Very Light)], BS [AEx = 11.3 ± 1.7 (Light), PEx = 10.3 ± 2.1 (Very Light)], HP [AEx = 13.1 ± 2.3 (Somewhat Hard), PEx = 12.3 ± 2.4 (Light - Somewhat Hard)]. Additionally, participants playing in the GymS experienced significantly higher levels of AEx [12.4 ± 2.3 (Light - Somewhat Hard)] and PEx [10.8 ± 2.5 (Very Light - Light)] compared to the LabS [AEx = 11.6 ± 1.8 (Light), PEx = 10.3 ± 2.6 (Very Light - Light)]. Conclusion: Perceptions of exertion may be lower than actual exertion during AVRG gameplay, and exertion levels can be influenced by the setting in which AVRGs are played. This may inform VR developers and health clinicians who aim to incorporate exercise/fitness regimens into upcoming ‘virtual worlds’ currently being developed at large scales (i.e., the “metaverse”).